Modulation of cellular immunity by Schistosoma mansoni in mice - Walsh, Caitríona (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2006)
Schistosoma mansoni is a trematode parasite that elicits a potent Th2 response in its mammalian host. Schistosomes are powerful stimulators and suppressors of the immune system, with these alterations in immune function permitting the parasite to live for up to 40 years in humans. In this thesis T cell responses during acute and chronic murine S. mansoni infection were addressed. A novel mechanism of immune modulation in a worm-only infection was identified, with cells from worm-infected mice having impaired T cell proliferation, that was restored by addition of IL-2. F4/80+ splenic macrophages from worm infected mice also induced anergy in naive CD4+ and CD8+ T cells. The inhibitory costimulatory molecule PD-L1 was shown to mediate this anergy. Levels of PD-L1 declined during S. mansoni worm infection, and this correlated with a reduction in anergy induced by the worm infection. This is the first demonstration that PD-L1 has been employed by a pathogen to undermine the immune system.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin